BUDAYA ORGANISASI DALAM MEMBANGUN KEMANDIRIAN PONDOK PESANTREN MODERN - Anis Mahatika; Jamilus Jamilus (Jurnal Isema : Islamic Educational Management, 2022)
This study aims to describe the organizational culture in building the independence of the Modern Islamic Boarding School Al-Kautsar Muhammadiyah Sarilamak Regency of Fifty Cities. This research uses a phenomenological approach. Data collection techniques used are unstructured interviews, observation, and documentation studies. Then the technique of collecting informants with snowball sampling technique. Furthermore, the data analysis technique used is the Miles and Huberman model, the stages of this model are data reduction, data presentation, and conclusion drawing and data verification. Meanwhile, to test the validity of the data, the researchers used data triangulation techniques. The results of the study show that the organizational culture applied in building the independence of Islamic boarding schools, namely 1) Instilling Islamic values that can increase the independence of students; 2) Applying language days to students; 3) Instilling the values of discipline; 4) Improve work ethic; 5) Forming the entrepreneurial spirit of students; 6) Establish nine business units to build pesantren independence; 7) Establishment of Sharia Microfinance Institutions for community empowerment and pesantren independence